Anti-Biofilm and Immunomodulatory Activities of Peptides That Inhibit Biofilms Formed by Pathogens Isolated from Cystic Fibrosis Patients - César de la Fuente-Núñez; Sarah C. Mansour; Zhejun Wang; Lucy Jiang; Elena B.M. Breidenstein; Melissa Elliott; Fany Reffuveille; David P. Speert; Shauna L. Reckseidler-Zenteno; Ya Shen; Markus Haapasalo; Robert E.W. Hancock (MDPI AG, 2014)
Cystic fibrosis (CF) patients often acquire chronic respiratory tract infections due to Pseudomonas aeruginosa and Burkholderia cepacia complex (Bcc) species. In the CF lung, these bacteria grow as multicellular aggregates termed biofilms. Biofilms demonstrate increased (adaptive) resistance to conventional antibiotics, and there are currently no available biofilm-specific therapies. Using plastic adherent, hydroxyapatite and flow cell biofilm models coupled with confocal and scanning electron microscopy, it was demonstrated that an anti-biofilm peptide 1018 prevented biofilm formation, eradicated mature biofilms and killed biofilms formed by a wide range of P. aeruginosa and B. cenocepacia clinical isolates. New peptide derivatives were designed that, compared to their parent peptide 1018, showed similar or decreased anti-biofilm activity against P. aeruginosa biofilms, but increased activity against biofilms formed by the Gram-positive bacterium methicillin resistant Staphylococcus aureus. In addition, some of these new peptide derivatives retained the immunomodulatory activity of 1018 since they induced the production of the chemokine monocyte chemotactic protein-1 (MCP-1) and suppressed lipopolysaccharide-mediated tumor necrosis factor-α (TNF-α) production by human peripheral blood mononuclear cells (PBMC) and were non-toxic towards these cells. Peptide 1018 and its derivatives provide promising leads for the treatment of chronic biofilm infections and hyperinflammatory lung disease in CF patients.